A new pygmy grasshopper species (Tetrigidae: Tetriginae) from Central India - Gupta, Sunil Kumar (Zootaxa, 2016)
Ergatettix subtruncatus sp. nov. is described from Durg district of Chhattisgarh, India. The new species is similar to Ergatettix callosus (Hancock, 1915), but differs from the latter by frontal cost bifurcation starts at the level of upper margin of compound eyes; median carina of vertex indistinct; posterior angle of lateral lobes of pronotum not broad, apex subtruncate, narrow; mid femur slender with small white hairs and 3indistinct lobes; dorsal valve of ovipositor less flattened. A distribution map of Ergatettix subtruncatus sp. nov. and a key to known species of the genus Ergatettix Kirby, 1914 from the Indian subcontinent is provided. The type specimens are deposited in the Central Entomological Laboratory (CEL), Zoological Survey of India, Kolkata.